High-energy-storage anti-ferroelectric multilayer capacitor with heterostructure and preparation method of high-energy-storage anti-ferroelectric multilayer capacitor

By adopting a heterostructure in antiferroelectric multilayer ceramic capacitors, combined with antiferroelectric material layers with larger electrostrains and smaller, the problem of difficult energy storage density and efficiency in the prior art is solved, and the problem of energy storage density and efficiency is realized. High energy storage density and high efficiency are taken into account, and the reliability of the device is improved.

CN119208013AActive Publication Date: 2024-12-27HUAZHONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411331641.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing antiferroelectric multi-layer ceramic capacitors are difficult to take into account energy storage efficiency while increasing the energy storage density, and are poor in reliability, which is prone to affect normal operation due to thermal breakdown.

Method used

Design of antiferroelectric multilayer capacitors with heterostructure, by combining antiferroelectric material layers with larger and smaller electrostrains in the multilayer antiferroelectric material layer, multilayers with different electrostrain characteristics are constructed Structure, the in-plane mismatch strain between the dielectric layers can be used to adjust the domain size and polarization characteristics, so as to achieve both high energy storage density and high energy storage efficiency.

Benefits of technology

It achieves a balance between high energy storage density and high energy storage efficiency, extends the service life of the device, and reduces Joule heat generation, which is suitable for the development trend of integration, miniaturization and lightweight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208013A_ABST
    Figure CN119208013A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electronic information materials and components, and discloses a high-energy-storage anti-ferroelectric multilayer capacitor with a heterostructure and a preparation method thereof.The anti-ferroelectric multilayer capacitor with the heterostructure comprises multiple anti-ferroelectric material layers stacked from bottom to top, and an electrode is arranged between every two adjacent anti-ferroelectric material layers; the plurality of anti-ferroelectric material layers simultaneously comprise anti-ferroelectric material layers with relatively large electrostrictive strain and anti-ferroelectric material layers with relatively small electrostrictive strain; and the upper layer and the lower layer adjacent to each anti-ferroelectric material layer with relatively large electrostrictive strain are anti-ferroelectric material layers with relatively small electrostrictive strain. According to the invention, the anti-ferroelectric material layers with large electrostrictive strain and the anti-ferroelectric material layers with small electrostrictive strain are used at the same time, and the upper layer and the lower layer adjacent to each anti-ferroelectric material layer with large electrostrictive strain are the anti-ferroelectric material layers with small electrostrictive strain. The obtained high-energy-storage anti-ferroelectric multilayer capacitor with the heterostructure has high energy storage density and high energy storage efficiency at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electronic information materials and components, and more specifically, relates to a high energy storage antiferroelectric multilayer ceramic capacitor with a heterogeneous structure and a preparation method thereof. Background Art

[0002] Dielectric capacitors, such as dielectric ceramic capacitors, are widely used in military fields such as aerospace, new weapons and equipment, as well as consumer and industrial fields such as mobile communications, new energy vehicles, and smart grids due to their ultra-high discharge power density. However, dielectric ceramic capacitors can only provide low energy storage density, which cannot meet the needs of electronic equipment to develop in the direction of integration, miniaturization and lightweight. Therefore, there is an urgent need to develop dielectric ceramic capacitors with high energy storage performance.

[0003] The key factor affecting the energy storage performance of dielectric ceramic capacitors is the energy storage dielectric material, which mainly includes linear dielectrics, ferroelectrics, relaxor ferroelectrics and antiferroelectrics. Among them, antiferroelectrics have a unique double hysteresis loop due to the antiferroelectric-ferroelectric phase transition induced by the electric field, and the dielectric constant increases with the increase of the electric field, which is considered to be an ideal energy storage medium. However, the antiferroelectric energy storage materials (such as lead zirconate-based materials) developed by the prior art, although they can usually improve the energy storage density by doping modification, often lead to a decrease in energy storage efficiency. In other words, it is difficult for such materials to take into account energy storage efficiency while improving energy storage density; due to the low energy storage efficiency, the device will generate more Joule heat when working, which is not conducive to the recycling of the device, thus putting forward higher requirements for energy storage efficiency. In addition, although the interdigital electrode structure of the antiferroelectric multilayer ceramic capacitor in the prior art helps to further improve the energy storage density, due to the small size and poor heat dissipation capacity of the multilayer ceramic capacitor, the heat generated by energy loss is more likely to cause thermal breakdown, thereby affecting the normal operation of the capacitor. Therefore, improving the energy storage efficiency can not only save costs, but also extend the service life of the device. In the context of energy conservation and emission reduction, it is of great significance to achieve a combination of high energy storage density and high energy storage efficiency. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a high-energy storage antiferroelectric multilayer capacitor with a heterogeneous structure and a preparation method thereof, wherein the structure of the multilayer antiferroelectric material layer is improved, and the multilayer antiferroelectric material layer is constructed using an antiferroelectric material layer with a larger electrostrain and an antiferroelectric material layer with a smaller electrostrain as the active layer of the device, so that except for the upper end surface and the lower end surface of the active layer, the upper antiferroelectric material layer and the lower antiferroelectric material layer adjacent to each antiferroelectric material layer with a larger electrostrain are both antiferroelectric material layers with a smaller electrostrain. The obtained heterogeneous structure high-energy storage antiferroelectric multilayer capacitor has both high energy storage density and high energy storage efficiency, which can effectively solve the problem that it is difficult to take into account both high energy storage density and high energy storage efficiency and poor reliability of the existing antiferroelectric multilayer capacitor.

[0005] To achieve the above object, according to one aspect of the present invention, there is provided an antiferroelectric multilayer capacitor with a heterogeneous structure, characterized in that it comprises a plurality of antiferroelectric material layers stacked from bottom to top, wherein electrodes are arranged on the upper and lower surfaces of each antiferroelectric material layer, and electrodes are shared between two adjacent antiferroelectric material layers;

[0006] The multilayer antiferroelectric material layer is prepared by the same sintering process, and according to the electro-strain size of each antiferroelectric material layer in the multilayer antiferroelectric material layer, the multilayer antiferroelectric material layer includes both antiferroelectric material layers with larger electro-strain and antiferroelectric material layers with smaller electro-strain; and, in the multilayer antiferroelectric material layer, except for the upper end face and the lower end face, the upper antiferroelectric material layer and the lower antiferroelectric material layer adjacent to each antiferroelectric material layer with larger electro-strain are both antiferroelectric material layers with smaller electro-strain;

[0007] Among them, the electrostrain S of the antiferroelectric material layer with larger electrostrain is greater than 0.20%, the electrostrain S of the antiferroelectric material layer with smaller electrostrain is less than or equal to 0.20%, and the electrostrain difference ΔS between the two is greater than 0.10%; the electrostrain S of each antiferroelectric material layer corresponds to the electric field strength corresponding to when the polarization intensity of each antiferroelectric material in the multi-layer antiferroelectric material layer reaches saturation, and the minimum electric field strength therein is used as the electrostrain test electric field, and each antiferroelectric material layer is subjected to an electrostrain test to obtain the result.

[0008] As a further preferred embodiment of the present invention, the antiferroelectric material layer with large electro-induced strain is (Pb 1-m- 1.5y Ba m La y )(Zr 0.6 Sn 0.4 ) 3 Antiferroelectric ceramic material, the antiferroelectric material used in the antiferroelectric material layer with small electro-induced strain is selected from (Pb1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 Antiferroelectric ceramic materials, (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Antiferroelectric ceramic materials; the values ​​of x, y, z, m, n, and p are all in the range of 0.02 to 0.06;

[0009] Note that (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 The antiferroelectric material layer of the antiferroelectric ceramic material is the A layer, which is made of (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 ) 3 The antiferroelectric material layer of the antiferroelectric ceramic material is the B layer, which is made of (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 The antiferroelectric material layer of the antiferroelectric ceramic material is the C layer, then,

[0010] The multilayer antiferroelectric material layer is an antiferroelectric material layer of 2 layers in total formed by stacking layer A-layer B, or an antiferroelectric material layer of 2 layers in total formed by stacking layer B-layer C, or an antiferroelectric material layer of 3 layers in total formed by stacking layer A-layer B-layer C, or an antiferroelectric material layer of 5 layers in total formed by stacking layer A-layer A-layer B-layer C-layer C, or an antiferroelectric material layer of 7 layers in total formed by stacking layer A-layer A-layer A-layer B-layer C-layer C-layer;

[0011] Alternatively, the multilayer antiferroelectric material layer is formed by periodically stacking layer A-layer B, or by periodically stacking layer B-layer C, or by periodically stacking layer A-layer B-layer C, or by periodically stacking layer A-layer A-layer B-layer C-layer C, or by periodically stacking layer A-layer A-layer A-layer B-layer C-layer C.

[0012] As a further preferred embodiment of the present invention, the thickness of each antiferroelectric material layer itself does not exceed 50 μm.

[0013] As a further preferred embodiment of the present invention, for the electrodes inside the multilayer antiferroelectric material layer, two adjacent electrodes are staggeredly distributed left and right to form an interdigitated electrode structure as a whole;

[0014] Antiferroelectric material sacrificial layers are stacked above and below the multi-layer antiferroelectric material layers.

[0015] According to another aspect of the present invention, the present invention provides a method for preparing the above-mentioned antiferroelectric multilayer capacitor having a heterostructure, characterized in that it comprises the following steps:

[0016] S1. Preparing antiferroelectric material powder with large electro-strain and antiferroelectric material powder with small electro-strain, respectively, and subjecting them to tape casting to obtain antiferroelectric material monolayer film with large electro-strain and antiferroelectric material monolayer film with small electro-strain; then, slicing and cutting these monolayer films, and printing metal as an electrode on the upper surface of the cut monolayer film by screen printing;

[0017] Among them, the antiferroelectric material with large electro-induced strain is (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 ) 3 Antiferroelectric ceramic material, the antiferroelectric material with small electro-induced strain is selected from (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 Antiferroelectric ceramic materials, (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Antiferroelectric ceramic materials; the values ​​of x, y, z, m, n, and p are all in the range of 0.02 to 0.06;

[0018] S2. stacking the single-layer films with electrodes from bottom to top, so that except for the upper end face and the lower end face, the upper layer and the lower layer adjacent to each antiferroelectric material single-layer film with large electro-strain are both antiferroelectric material single-layer films with small electro-strain, and then hot pressing to obtain a capacitor green body with a multi-layer heterostructure, and performing cold isostatic pressing treatment;

[0019] S3. The green body after cold isostatic pressing is subjected to binder removal treatment to remove organic matter introduced during the casting process, and then sintering treatment is performed. After cooling, silver electrode slurry is coated on the left and right end surfaces, and the end electrodes are prepared by sintering to obtain an antiferroelectric multilayer capacitor with a heterogeneous structure.

[0020] As a further preferred embodiment of the present invention, in step S2, before the hot pressing, it also includes making a sacrificial layer of antiferroelectric material above and below the stacked structure;

[0021] In step S3, the burning end is specifically heated to 600°C at 5°C / min, kept at that temperature for 10-30min, and cooled along with the furnace.

[0022] As a further preferred embodiment of the present invention, in step S1, (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 ) 3 Antiferroelectric ceramic materials are based on (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 ) 3 Nominal chemical dosage ratio of metal elements PbO, BaCO 3 ,La 2 O 3 、ZrO 2 and SnO 2 The raw materials are mixed, followed by a first ball milling process and a first drying process; then pre-calcined, and a second ball milling process and a second drying process are performed to obtain (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 ) 3 Antiferroelectric ceramic materials;

[0023] (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 Antiferroelectric ceramic materials are based on (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3Nominal chemical dosage ratio of metal elements PbO, BaCO 3 ,La 2 O 3 、ZrO 2 SnO 2 and TiO 2 The raw materials are mixed, followed by a first ball milling process and a first drying process; then pre-calcined, and a second ball milling process and a second drying process are performed to obtain (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 Antiferroelectric ceramic materials;

[0024] (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Antiferroelectric ceramic materials are based on (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Nominal chemical dosage ratio of metal elements PbO, CaCO 3 ,La 2 O 3 、ZrO 2 and SnO 2 The raw materials are mixed, followed by a first ball milling process and a first drying process; then pre-calcined, and a second ball milling process and a second drying process are performed to obtain (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Antiferroelectric ceramic materials.

[0025] As a further preference of the present invention, for each antiferroelectric ceramic material:

[0026] The ball milling speed of the first ball milling treatment is 200-500 r / min, and the ball milling time is 3-48 h; the drying temperature of the first drying is 50-110° C., and the drying time is 3-12 h;

[0027] The pre-burning temperature is 800-950°C and the pre-burning time is 2-5h;

[0028] The ball milling speed of the second ball milling treatment is 200-500 r / min, and the ball milling time is 3-48 h; the drying temperature of the second drying is 50-110° C., and the drying time is 3-12 h.

[0029] As a further preferred embodiment of the present invention, in step S1, the casting process is to disperse the corresponding antiferroelectric ceramic material powder together with the dispersant, defoamer, binder and plasticizer in a solvent, ball mill and mix at a speed of 200 to 500 r / min for 3 to 48 hours to obtain a casting slurry, vacuum degassing for 10 to 60 minutes, and casting the casting slurry on a casting machine at a speed of 0.5 to 5 m / min and drying to obtain a single-layer film;

[0030] Preferably, the thickness of the single-layer film obtained by casting is 5 to 50 μm.

[0031] As a further preferred embodiment of the present invention, in step S2, the metal is silver, palladium, copper, nickel, platinum or an alloy of two or more thereof; the thickness of the screen-printed electrode is 0.5 to 3 μm;

[0032] The hot pressing treatment temperature of the hot pressing is 60-80°C, the pressure value is 2-20Mpa, and the holding time is 1-30min;

[0033] The pressure value of cold isostatic pressing treatment is 50-200Mpa, and the holding time is 10-30min;

[0034] In step S3, the debinding treatment is carried out at a temperature of 500 to 600° C. for 30 to 300 minutes;

[0035] The sintering process is carried out at a temperature of 1100-1200° C. for 2-6 hours.

[0036] Through the above technical scheme conceived by the present invention, compared with the prior art, based on the heterostructure design strategy, the present invention selects antiferroelectric materials with different electrostrain properties (wherein the electrostrain S of the antiferroelectric material with larger electrostrain is greater than 0.20%, the electrostrain S of the antiferroelectric material with smaller electrostrain is less than 0.20%, and the strain difference ΔS is greater than 0.10%) to construct a heterostructure, so that the tensile strain and the compressive strain are accurately distributed in the corresponding dielectric layer. The antiferroelectric multilayer capacitor prepared by the present invention has interlayer strain interaction, the in-plane mismatch tensile strain will reduce the domain size and reduce the loss caused by domain reversal, and the in-plane mismatch compressive strain will increase the domain size and improve the polarization strength, which can decouple the inherent conflict between high polarization and low loss (low ΔE), and achieve high energy storage density, high energy storage efficiency and excellent reliability.

[0037] Most of the research in the prior art focuses on optimizing the performance of a single material, while ignoring the strain coordination in the multilayer structure. Taking the lead zirconate-based antiferroelectric ceramic material as an example, the prior art reports a variety of lead zirconate-based antiferroelectric ceramic materials. Based on the present invention, a heterogeneous structure of a multilayer antiferroelectric ceramic material layer including an antiferroelectric ceramic material layer with a larger electro-induced strain and an antiferroelectric ceramic material layer with a smaller electro-induced strain can be constructed according to the different electro-induced strains of various lead zirconate-based materials. Among them, the antiferroelectric ceramic material layer with a larger electro-induced strain is made of (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 ) 3 Antiferroelectric ceramic materials (0.02≤m≤0.06, 0.02≤y≤0.06; such as (Pb 0.98-1.5y Ba 0.02 La y )(Zr 0.6 Sn 0.4 ) 3 ), the antiferroelectric ceramic material used in the antiferroelectric ceramic material layer with small electro-induced strain is selected from (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 Antiferroelectric ceramic materials (0.02≤n≤0.06, 0.02≤x≤0.06; such as (Pb 0.96-1.5x Ba 0.04 La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 ), (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Antiferroelectric ceramic materials (0.02≤p≤0.06, 0.02≤z≤0.06; such as (Pb 0.95-1.5z Ca 0.06 La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3); and, except for the upper end face and the lower end face, the upper antiferroelectric ceramic material layer and the lower antiferroelectric ceramic material layer adjacent to each antiferroelectric ceramic material layer with larger electrostrain are both antiferroelectric ceramic material layers with smaller electrostrain. A multilayer ceramic capacitor is formed by the antiferroelectric material layer composition with different electrostrains, thereby utilizing the antiferroelectric-ferroelectric phase transition characteristics induced by the electric field and the different electrostrain characteristics (that is, by utilizing the in-plane mismatch strain between the dielectric layers during the charging and discharging process to adjust the domain size, domain reversal behavior and polarization characteristics of the antiferroelectric material), thereby significantly improving the energy storage efficiency while maintaining a high energy storage density, and improving the reliability of the capacitor.

[0038] The heterostructure multilayer capacitor prepared by the present invention has interlayer strain interaction. During the charge and discharge process, the in-plane mismatch strain between dielectric layers is used to adjust the domain size, domain reversal behavior and polarization characteristics of the antiferroelectric material, thereby simultaneously improving the energy storage density and energy storage efficiency of the capacitor and extending the service life of the device. This is of great significance for the development of high-performance antiferroelectric multilayer capacitors.

[0039] Taking the lead zirconate-based antiferroelectric ceramic material as an example, unlike the prior art where the energy storage density and energy storage efficiency of a single lead zirconate-based material cannot be taken into account, the present invention can take into account both energy storage density and energy storage efficiency through the structural design of multiple antiferroelectric material layers with different electro-induced strains, thereby obtaining a capacitor with high energy storage density and high energy storage efficiency. Taking Table 1 below as an example, the energy storage density of the device in Example 1 obtained by the present invention is 20.0 J cm -3 , the energy storage efficiency is 95.2%, while Comparative Examples 1, 2, and 3, which use a single material to construct a multi-layer antiferroelectric ceramic material layer, either have good energy storage density and unsatisfactory energy storage efficiency, or have good energy storage efficiency and unsatisfactory energy storage density, and they cannot take both into account. Higher energy storage efficiency also means a decrease in the proportion of Joule heat generated, which reduces the requirements for heat dissipation, and is very consistent with the development trend of integration, miniaturization, and lightweight. Moreover, as shown in Table 1 below, Comparative Examples 1, 2, and 3, which use a single material to construct a multi-layer antiferroelectric ceramic material layer, either have a high saturation polarization intensity or a high breakdown electric field intensity, and the two are mutually exclusive and cannot be taken into account; while the device of Example 1 obtained based on the present invention has both high saturation polarization intensity and high breakdown electric field intensity. Of course, in addition to the antiferroelectric ceramic material based on the lead zirconate system, the present invention can also use other antiferroelectric materials, as long as the electrostrain of each antiferroelectric material layer in the formed multilayer antiferroelectric material layer is large and small (the electrostrain of the larger one is S>0.20%, the electrostrain of the smaller one is S≤0.20%, and the strain difference ΔS between the two is>0.10%), and the sintering temperature zones of the antiferroelectric materials are compatible, so that the multilayer antiferroelectric material layer can be prepared by the same sintering process (for example, (Pb 1-m-1.5y Bam La y )(Zr 0.6 Sn 0.4 ) 3 ,(Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 ,(Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Taking the material as an example, the value range of x, y, z, m, n, and p is 0.02-0.06, and their sintering temperatures are all between 1200 and 1300°C; of course, if the casting process is adopted first and then sintering is performed, the sintering temperature can be lowered, for example, a sintering temperature of 1100-1200°C can be adopted).

[0040] In addition, the method of the present invention has a simple preparation process and good production process compatibility, which is conducive to industrial mass production.

[0041] In summary, the present invention constructs an antiferroelectric multilayer capacitor with a heterogeneous structure, and the obtained device has the characteristics of high energy storage density and high energy storage efficiency. Taking the use of lead zirconate-based antiferroelectric ceramic materials as an example, it effectively solves the problem that it is difficult to take both high energy storage density and high energy storage efficiency into account and the reliability is poor in lead zirconate-based antiferroelectric multilayer ceramic capacitors under the prior art, and provides a new design and preparation idea for the research and development of antiferroelectric multilayer ceramic capacitors with high energy storage density, high energy storage efficiency and excellent reliability, promotes the practical application of lead zirconate-based antiferroelectric ceramic materials, and helps to promote the development of electronic components towards integration, miniaturization and lightweight. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The structure diagram of the single antiferroelectric multilayer ceramic capacitor prepared in Comparative Example 1 of the present invention is shown in FIG. Comparative Examples 2 and 3 also use the same structure, except that "medium A" is replaced with a corresponding dielectric material (in the present invention, (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 The material is recorded as A, and (Pb 1-m-1.5y Ba m La y )(Zr 0.6Sn 0.4 ) 3 The material is denoted as B, (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O 3 The material is recorded as C).

[0043] Figure 2 Schematic diagram of the structure of the heterostructure antiferroelectric multilayer ceramic capacitor prepared in Examples 1 and 3 of the present invention.

[0044] Figure 3 Schematic diagram of the structure of the heterostructure antiferroelectric multilayer ceramic capacitor prepared in Examples 2 and 4 of the present invention.

[0045] Figure 4 Cross-sectional scanning electron microscope (SEM) images of the PB4L4ZST antiferroelectric multilayer ceramic capacitor prepared in comparative example 1 of the present invention, the PB2L2ZS antiferroelectric multilayer ceramic capacitor prepared in comparative example 2, the PC6L2ZS antiferroelectric multilayer ceramic capacitor prepared in comparative example 3, and the heterostructure antiferroelectric multilayer ceramic capacitor prepared in Example 1 after sintering.

[0046] Figure 5 The energy storage density and energy storage efficiency of the PB4L4ZST antiferroelectric multilayer ceramic capacitor prepared in comparative example 1, the PB2L2ZS antiferroelectric multilayer ceramic capacitor prepared in comparative example 2, the PC6L2ZS antiferroelectric multilayer ceramic capacitor prepared in comparative example 3, and the heterostructure antiferroelectric multilayer ceramic capacitor prepared in Example 1 under the maximum electric field are shown in the figure. The specific values ​​(unit kV cm -1 ) is the corresponding breakdown electric field strength.

[0047] Figure 6 This is a cyclic stability graph of the energy storage density and energy storage efficiency of the heterostructure antiferroelectric multilayer ceramic capacitor prepared in Example 1 of the present invention.

[0048] Figure 7 The capacitors prepared in Comparative Examples 1, 2 and 3 are 350 kV cm -1 The electrostrain curves obtained by electrostrain testing under electric field strength conditions (i.e., the electrostrain curves of the three antiferroelectric materials PB4L4ZST, PB2L2ZS, and PC6L2ZS). DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0050] In the following examples, unless otherwise specified, all reagents used are commercially available reagents; all detection means and methods used are conventional detection means and methods in the art. The quantitative tests in the following examples were repeated three times, and the data are the average or average ± standard deviation of the three repeated experiments.

[0051] The following embodiments focus on the multilayer antiferroelectric material layers (i.e., the active layer, the antiferroelectric material layer with printed electrodes) in the antiferroelectric multilayer capacitor. Similar to conventional operations, antiferroelectric material sacrificial layers (i.e., antiferroelectric material layers without printed electrodes, used to protect the middle active layer to avoid sintering and bending; the antiferroelectric material used in the sacrificial layer is the same as the antiferroelectric material system used in the active layer, i.e., the lead zirconate-based system) can be stacked above and below the multilayer antiferroelectric material layers. In other words, the middle part of the device is the active layer, and the upper and lower parts are the sacrificial layers; for the active layer, electrodes are arranged on the upper and lower surfaces of each active layer, the upper and lower surfaces of the middle layer share electrodes with the adjacent layers, and a separate electrode is arranged on the upper surface of the uppermost layer and the lower surface of the lowermost layer of the active layer; the sacrificial layers on the upper and lower sides are stacked by antiferroelectric film strips without printed electrodes.

[0052] Comparative Example 1

[0053] This comparative example is prepared by referring to the prior art (Pb 0.9 Ba 0.04 La 0.04 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 (PB4L4ZST for short) antiferroelectric ceramic material, and further prepare PB4L4ZST antiferroelectric multilayer ceramic capacitors. Specifically comprising the following steps:

[0054] (1) According to the chemical formula (Pb 0.9 Ba 0.04 La 0.04 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 The stoichiometric ratio of each element in the raw materials PbO, BaCO 3 ,La 2 O3 、ZrO 2 SnO 2 and TiO 2 , ball milling mixing, the ball milling speed is 400r / min, the ball milling time is 6h, and then drying, the drying temperature is 80℃, and the drying time is 6h to obtain a mixed powder;

[0055] (2) The PB4L4ZST mixed powder was pre-calcined at 850°C for 3 h, and subjected to secondary ball milling at a ball milling speed of 400 r / min for 6 h, followed by drying at a drying temperature of 80°C for 6 h;

[0056] (3) The PB4L4ZST pre-calcined powder was mixed with a dispersant, a defoamer, a binder, a plasticizer and a solvent by ball milling at a speed of 400 r / min for 6 h to obtain a casting slurry (the formula of the casting slurry can be set with reference to the relevant prior art. In each comparative example and embodiment of the present invention including this example, the solvent is a mixed solution of anhydrous ethanol and toluene, which is used to dissolve the added organic matter; the binder is a mixed solution of polyvinyl butyral and ethanol, which is used to wrap the ceramic powder particles and form a three-dimensional resin frame after curing, so that the casting film has a certain degree of flexibility; the defoamer is a three-dimensional resin frame. Oleic acid glyceride is used to eliminate some bubbles generated during the stirring process; the dispersant is polyethylene glycol, which is used to disperse the ceramic particles to facilitate the wrapping of the binder; the plasticizer is butyl benzyl phthalate, which is used to improve the flexibility and ductility of the cast film tape for processing and storage; the pre-sintered and ball-milled powder can be mixed with the above-mentioned organic matter in a certain proportion by ball milling to obtain a mixed solution), vacuum degassing for 30 minutes, and the cast slurry is cast on a casting machine at a speed of 1m / min and dried to obtain a cast film with a thickness of 20μm, forming a PB4L4ZST antiferroelectric single-layer thick film;

[0057] (4) Slicing the PB4L4ZST antiferroelectric single-layer thick film, and printing 70Ag / 30Pd alloy as an inner electrode layer on the upper surface of the cut thick film by screen printing (of course, in addition to the commonly used 70Ag / 30Pd, other common metal electrode materials such as silver, palladium, copper, nickel, platinum or their alloys can also be used), and the thickness of the inner electrode layer is 1 μm;

[0058] (5) stacking the PB4L4ZST antiferroelectric single-layer thick film with electrodes to form an interdigitated electrode structure, followed by hot pressing at a temperature of 70° C., a pressure of 5 MPa, and a holding time of 10 min; cold isostatic pressing at a pressure of 100 MPa and a holding time of 20 min, to obtain an antiferroelectric multilayer ceramic capacitor green body with a single structure;

[0059] (6) The green body after cold isostatic pressing is placed in a muffle furnace, debinded at 600°C for 120 min (debinding is to volatilize the organic matter introduced by the casting operation, thereby facilitating the dense growth of the ceramic in the subsequent sintering process), sintered at 1120-1150°C for 300 min, and taken out after naturally cooling to room temperature. Silver paste is applied to both ends as terminal electrodes and silver is burned (i.e., silver electrode paste is applied to both ends of the sintered multilayer ceramic capacitor, and the end is burned. The process is: heating to 600°C at 5°C / min, keeping warm for 10-20 min, and cooling with the furnace; the same below), so as to obtain the PB4L4ZST antiferroelectric multilayer ceramic capacitor (structure as shown in FIG. Figure 1 shown).

[0060] Comparative Example 2

[0061] This comparative example is prepared by referring to the prior art (Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 3 (PB2L2ZS for short) antiferroelectric ceramic material, and further prepare PB2L2ZS antiferroelectric multilayer ceramic capacitors. Specifically comprising the following steps:

[0062] (1) According to the chemical formula (Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 3 The stoichiometric ratio of each element in the raw materials PbO, BaCO 3 ,La 2 O 3 、ZrO 2 and SnO 2 , ball milling mixing, the ball milling speed is 400r / min, the ball milling time is 6h, and then drying, the drying temperature is 80℃, and the drying time is 6h to obtain a mixed powder;

[0063] (2) The PB2L2ZS mixed powder was pre-calcined at 900°C for 3 h, and subjected to secondary ball milling at a ball milling speed of 400 r / min for 6 h, followed by drying at a drying temperature of 80°C for 6 h;

[0064] (3) The PB2L2ZS pre-calcined powder was mixed with a dispersant, a defoamer, a binder, a plasticizer and a solvent by ball milling at a speed of 400 r / min for 6 h to obtain a casting slurry, and the casting slurry was vacuum defoamed for 30 min. The casting slurry was cast on a casting machine at a speed of 1 m / min and dried to obtain a casting film with a thickness of 20 μm, thereby forming a PB2L2ZS antiferroelectric single-layer thick film;

[0065] (4) Slicing the PB2L2ZS antiferroelectric single-layer thick film, and printing 70Ag / 30Pd alloy as an inner electrode layer on the surface of the cut thick film by screen printing, and the thickness of the inner electrode layer is 1 μm;

[0066] (5) The PB2L2ZS antiferroelectric single-layer thick film with electrodes is staggered to form an interdigitated electrode structure, and then hot pressed at a temperature of 70°C, a pressure of 5 MPa, and a holding time of 10 min; the pressure of cold isostatic pressing is 100 MPa, and the holding time is 20 min, to obtain an antiferroelectric multilayer ceramic capacitor green body with a single structure;

[0067] (6) The green body after cold isostatic pressing is placed in a muffle furnace, debinded at 600° C. for 120 min, sintered at 1120-1150° C. for 300 min, and taken out after naturally cooling to room temperature. Silver paste is applied to both ends as terminal electrodes, and silver is fired to obtain the PB2L2ZS antiferroelectric multilayer ceramic capacitor (structure as shown in FIG. Figure 1 shown).

[0068] Comparative Example 3

[0069] This comparative example is prepared by referring to the prior art (Pb 0.92 Ca 0.06 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 (abbreviated as PC6L2ZS) antiferroelectric ceramic material, and further prepare PC6L2ZS antiferroelectric multilayer ceramic capacitors. Specifically comprising the following steps:

[0070] (1) According to the chemical formula (Pb 0.92 Ca 0.06 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 The stoichiometric ratio of each element in the raw materials PbO, CaCO 3 ,La 2 O 3 、ZrO 2 and SnO2 , ball milling mixing, the ball milling speed is 400r / min, the ball milling time is 6h, and then drying, the drying temperature is 80℃, and the drying time is 6h to obtain a mixed powder;

[0071] (2) The PC6L2ZS mixed powder was pre-calcined at 900°C for 3h, and subjected to secondary ball milling at a ball milling speed of 400r / min for 6h, followed by drying at a drying temperature of 80°C for 6h;

[0072] (3) The PC6L2ZS pre-calcined powder was mixed with a dispersant, a defoamer, a binder, a plasticizer and a solvent by ball milling at a speed of 400 r / min for 6 h to obtain a casting slurry, and the casting slurry was vacuum defoamed for 30 min. The casting slurry was cast on a casting machine at a speed of 1 m / min and dried to obtain a casting film with a thickness of 20 μm, thereby forming a PC6L2ZS antiferroelectric single-layer thick film;

[0073] (4) Slicing the PC6L2ZS antiferroelectric single-layer thick film, and printing 70Ag / 30Pd alloy as an inner electrode layer on the surface of the cut thick film by screen printing, and the thickness of the inner electrode layer is 1 μm;

[0074] (5) The PC6L2ZS antiferroelectric single-layer thick film with electrodes is staggered to form an interdigitated electrode structure, and then hot pressed at a temperature of 70°C, a pressure of 5 MPa, and a holding time of 10 min; the cold isostatic pressing pressure is 100 MPa and the holding time is 20 min, thereby obtaining an antiferroelectric multilayer ceramic capacitor green body with a single structure;

[0075] (6) The green body after cold isostatic pressing is placed in a muffle furnace, debinded at 600° C. for 120 min, sintered at 1120-1150° C. for 300 min, and taken out after naturally cooling to room temperature. Silver paste is applied to both ends as terminal electrodes, and silver is fired to obtain the PC6L2ZS antiferroelectric multilayer ceramic capacitor (structure as shown in FIG. Figure 1 shown).

[0076] Example 1

[0077] This embodiment provides a heterostructure (Pb) having an "ABC" periodic cycle (the period of the cycle is 2). 0.9 Ba 0.04 La 0.04 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 -(Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.6 Sn0.4 ) 3 -(Pb 0.92 Ca 0.06 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 (PB4L4ZST-PB2L2ZS-PC6L2ZS for short) antiferroelectric multilayer ceramic capacitor and its preparation method. Specifically comprising the following steps:

[0078] (1) Prepare (Pb 0.9 Ba 0.04 La 0.04 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 ,(Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 3 , and (Pb 0.92 Ca 0.06 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 Antiferroelectric powder, and the preparation method is consistent with the method in step (1) of Comparative Examples 1, 2 and 3 respectively;

[0079] (2) PB4L4ZST, PB2L2ZS and PC6L2ZS powders were pre-calcined and ball-milled for a second time, and then dried. The specific methods were the same as those in step (2) of Comparative Examples 1, 2 and 3, respectively;

[0080] (3) The PB4L4ZST, PB2L2ZS and PC6L2ZS pre-calcined powders are respectively mixed with a dispersant, a defoamer, a binder, a plasticizer and a solvent by ball milling, and then subjected to tape casting treatment. The specific method is the same as the method in step (3) of comparative examples 1, 2 and 3, respectively, to finally form antiferroelectric single-layer thick films of PB4L4ZST, PB2L2ZS and PC6L2ZS;

[0081] (4) Slicing the PB4L4ZST, PB2L2ZS and PC6L2ZS antiferroelectric single-layer thick films, and printing 70Ag / 30Pd alloy as an inner electrode layer on the surface of the cut thick films by screen printing, and the thickness of the inner electrode layer is 1 μm;

[0082] (5) stacking and hot pressing and cold isostatic pressing of PB4L4ZST, PB2L2ZS and PC6L2ZS antiferroelectric single-layer thick films with electrodes in an "ABC" cycle (the cycle is 2; i.e., ABCABC has a total of 6 layers), and the specific methods are respectively consistent with the methods in step (5) of comparative examples 1, 2 and 3, and finally obtaining an antiferroelectric multilayer ceramic capacitor green body with a heterogeneous structure;

[0083] (6) The green body after cold isostatic pressing is placed in a muffle furnace for debinding and sintering. The specific methods are the same as those in step (6) of comparative examples 1, 2 and 3. After naturally cooling to room temperature, the green body is taken out, silver paste is applied to both ends as terminal electrodes, and silver is fired to obtain the PB4L4ZST-PB2L2ZS-PC6L2ZS antiferroelectric multilayer ceramic capacitor with a heterostructure (structure as shown in FIG. Figure 2 shown).

[0084] Example 2

[0085] This embodiment provides a heterostructure (Pb) having an "AABCC" periodic cycle (the period of the cycle is 2). 0.9 Ba 0.04 La 0.04 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 -(Pb 0.9 Ba 0.04 La 0.04 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 -(Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 3 -(Pb 0.92 Ca 0.06 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 -(Pb 0.92 Ca 0.06 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 (abbreviated as PB4L4ZST-PB4L4ZST-PB2L2ZS-PC6L2ZS-PC6L2ZS) antiferroelectric multilayer ceramic capacitor and its preparation method.

[0086] Compared with Example 1, the present embodiment is different in that: Step (5) stacks the antiferroelectric single-layer thick film with electrodes in an "AABCC" cycle (cycle period is 2; that is, AABCCAABCC has 10 layers in total) to form an interdigitated electrode structure, followed by hot pressing, the hot pressing temperature is 70°C, the pressure value is 5Mpa, and the holding time is 10min; the cold isostatic pressing pressure value is 100Mpa, and the holding time is 20min, to obtain an antiferroelectric multilayer ceramic capacitor green body with a heterogeneous structure; the remaining steps are the same as Example 1. The structure of the PB4L4ZST-PB4L4ZST-PB2L2ZS-PC6L2ZS-PC6L2ZS antiferroelectric multilayer ceramic capacitor is as follows: Figure 3 shown.

[0087] Example 3

[0088] This embodiment provides a heterostructure (Pb) having an "ABC" periodic cycle (the period of the cycle is 2). 0.95 Ba 0.02 La 0.02 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 -(Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 3 -(Pb 0.96 Ca 0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 (abbreviated as PB2L2ZST-PB2L2ZS-PC2L2ZS) antiferroelectric multilayer ceramic capacitor and its preparation method.

[0089] The difference between this embodiment and embodiment 1 is that: step (1) is carried out according to the chemical formula (Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 ,(Pb 0.95 Ba 0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 3 and (Pb 0.96 Ca0.02 La 0.02 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 The stoichiometric ratio of each element in the raw materials PbO, BaCO 3 、CaCO 3 ,La 2 O 3 、ZrO 2 SnO 2 and TiO 2 , ball milled and mixed in batches, and the remaining steps are the same as in Example 1. The structure of the PB2L2ZST-PB2L2ZS-PC2L2ZS antiferroelectric multilayer ceramic capacitor is as follows Figure 2 shown.

[0090] Example 4

[0091] This embodiment provides a heterostructure (Pb) having an "AABCC" periodic cycle (the period of the cycle is 2). 0.85 Ba 0.06 La 0.06 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 -(Pb 0.85 Ba 0.06 La 0.06 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 -(Pb 0.85 Ba 0.06 La 0.06 )(Zr 0.6 Sn 0.4 ) 3 -(Pb 0.86 Ca 0.06 La 0.06 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 -(Pb 0.86 Ca 0.06 La 0.06 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 (abbreviated as PB6L6ZST-PB6L6ZST-PB6L6ZS-PC6L6ZS-PC6L6ZS) antiferroelectric multilayer ceramic capacitor and its preparation method.

[0092] The difference between this embodiment and embodiment 2 is that: step (1) is carried out according to the chemical formula (Pb 0.85 Ba 0.06 La 0.06 )(Zr 0.65 Sn 0.3 Ti 0.05 ) 3 ,(Pb 0.85 Ba 0.06 La 0.06 )(Zr 0.6 Sn 0.4 ) 3 and (Pb 0.86 Ca 0.06 La 0.06 )(Zr 0.6 Sn 0.4 ) 0.995 O 3 The stoichiometric ratio of each element in the raw materials PbO, BaCO 3 、CaCO 3 ,La 2 O 3 、ZrO 2 SnO 2 and TiO 2 , ball milling and mixing in batches, and the remaining steps are the same as those in Example 2. The structure of the PB6L6ZST-PB6L6ZST-PB6L6ZS-PC6L6ZS-PC6L6ZS antiferroelectric multilayer ceramic capacitor is as follows Figure 3 shown.

[0093] Result analysis:

[0094] The performance of the antiferroelectric multilayer ceramic capacitors prepared in Comparative Examples 1, 2, 3 and Example 1 was tested. The test results are shown in Table 1.

[0095] Table 1: Performance comparison table of comparative examples 1, 2, 3 and embodiment 1

[0096]

[0097] It can be seen from the above table that the heterostructure antiferroelectric multilayer ceramic capacitor prepared by the preparation method of the present invention has excellent energy storage performance.

[0098] Figure 4 The cross-sectional SEM images of the antiferroelectric multilayer ceramic capacitors of Comparative Example 1 (PB4L4ZST), Comparative Example 2 (PB2L2ZS), Comparative Example 3 (PC6L2ZS) and Example 1 (PB4L4ZST-PB2L2ZS-PC6L2ZS) after sintering are shown in FIG. It can be seen from the figure that the ceramic has a dense microstructure and a clear metal electrode-ceramic interface.

[0099] Figure 5 The energy storage density and energy storage efficiency of the antiferroelectric multilayer ceramic capacitors of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 under the maximum electric field are shown in the figure. It can be seen from the figure that Comparative Example 1 has a lower energy storage density (10.5 J cm -3 ), comparative example 2 has a lower energy storage efficiency (82.2%), comparative example 3 has a lower energy storage efficiency (84.1%), and the heterostructured PB4L4ZST-PB2L2ZS-PC6L2ZS antiferroelectric multilayer ceramic capacitor has a high energy storage density (20.0 J cm -3 ) and high energy storage efficiency (95.2%).

[0100] Figure 6 The energy storage density and energy storage efficiency of the heterostructure antiferroelectric multilayer ceramic capacitor prepared in Example 1 of the present invention are shown in the cyclic stability spectrum. As can be seen from the figure, Example 1 has a high energy storage efficiency of 500 kV cm -1 Under an applied electric field, after 100,000 cycles of charge and discharge, the energy storage density changes within a range of <4%, and the energy storage efficiency remains at ~94%, indicating that Example 1 has excellent cycle stability and is conducive to practical applications.

[0101] Figure 7 The electrostrain curves of the antiferroelectric multilayer ceramic capacitors obtained in Comparative Examples 1, 2, and 3 are shown in the figure. As can be seen from the figure, the electrostrains of PB4L4ZST, PB2L2ZS, and PC6L2ZS are 0.16%, 0.27%, and 0.10%, respectively. PB4L4ZST and PC6L2ZS meet the characteristics of smaller electrostrain, PB2L2ZS meets the characteristics of larger electrostrain, and the difference in electrostrain all meets the requirement of >0.10%.

[0102] The above embodiments are merely examples, and it is sufficient as long as the upper antiferroelectric ceramic material layer and / or the lower antiferroelectric ceramic material layer adjacent to each antiferroelectric ceramic material layer with a larger electro-strain (corresponding to using material B) is an antiferroelectric ceramic material layer with a smaller electro-strain (e.g., material A, material C); for example, except Figure 2 The "ABC" cycle shown, Figure 3 In addition to the "AABCC" cycle shown, "AB" cycle, "BC" cycle, etc. can also be used; for example, considering that material A and material C can improve energy storage efficiency, other deformation forms such as "AAABCCC" periodic stacking can be further adopted; the cycle period n can be a positive integer greater than 1; of course, the periodic cycle form can also be not adopted (corresponding cycle period n = 1). In addition, the preparation process of antiferroelectric powder materials, the burn-in process of capacitors, the materials and preparation processes of sacrificial layers, etc. can all be carried out with reference to the existing technology.

[0103] In addition, the above embodiment takes the preparation of the antiferroelectric ceramic material layer thick film by the tape casting method as an example (thickness 1 to 50 μm). If the antiferroelectric ceramic material films of different thicknesses are used, they can also obtain antiferroelectric multilayer ceramic capacitors with heterogeneous structures, while improving the energy storage density and energy storage efficiency; and the smaller the thickness of the film, the greater the breakdown electric field strength, which is conducive to further improving the energy storage density. Of course, in addition to the antiferroelectric ceramic material, the present invention can also use other antiferroelectric materials to obtain antiferroelectric multilayer capacitors with heterogeneous structures, as long as the electrostrain of each antiferroelectric material layer in the formed multilayer antiferroelectric material layer is large and the other is small (the electrostrain of the larger electrostrain is S>0.20%, the electrostrain of the smaller electrostrain is S≤0.20%, and the strain difference ΔS between the two is>0.10%), and the sintering temperature zones of each antiferroelectric material are compatible, so that the multilayer antiferroelectric material layer can be prepared by the same sintering process.

[0104] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An antiferroelectric multilayer capacitor having a heterostructure, characterized in that: It comprises a plurality of antiferroelectric material layers stacked from bottom to top, wherein electrodes are arranged on the upper surface and the lower surface of each antiferroelectric material layer, and two adjacent antiferroelectric material layers share electrodes; The multilayer antiferroelectric material layer is prepared by the same sintering process, and according to the electro-strain size of each antiferroelectric material layer in the multilayer antiferroelectric material layer, the multilayer antiferroelectric material layer includes both antiferroelectric material layers with larger electro-strain and antiferroelectric material layers with smaller electro-strain; and, in the multilayer antiferroelectric material layer, except for the upper end face and the lower end face, the upper antiferroelectric material layer and the lower antiferroelectric material layer adjacent to each antiferroelectric material layer with larger electro-strain are both antiferroelectric material layers with smaller electro-strain; Among them, the electrostrain S of the antiferroelectric material layer with larger electrostrain is greater than 0.20%, the electrostrain S of the antiferroelectric material layer with smaller electrostrain is less than or equal to 0.20%, and the electrostrain difference ΔS between the two is greater than 0.10%; the electrostrain S of each antiferroelectric material layer corresponds to the electric field strength corresponding to when the polarization intensity of each antiferroelectric material in the multi-layer antiferroelectric material layer reaches saturation, and the minimum electric field strength therein is used as the electrostrain test electric field, and each antiferroelectric material layer is subjected to an electrostrain test to obtain the result.

2. The antiferroelectric multilayer capacitor having a heterostructure as claimed in claim 1, characterized in that: The antiferroelectric material layer with large electro-induced strain is made of (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 )O3 antiferroelectric ceramic material, the antiferroelectric material used in the antiferroelectric material layer with small electro-induced strain is selected from (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 )O3 antiferroelectric ceramic materials, (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O3 antiferroelectric ceramic material; the value ranges of x, y, z, m, n, and p are all 0.02 to 0.06; Note that (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 )O3 antiferroelectric ceramic material has an antiferroelectric material layer as layer A, using (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 )O3 antiferroelectric ceramic material has an antiferroelectric material layer as the B layer, using (Pb 1.01-p- 1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 The antiferroelectric material layer of the O3 antiferroelectric ceramic material is the C layer, then, The multilayer antiferroelectric material layer is an antiferroelectric material layer of 2 layers in total formed by stacking layer A-layer B, or an antiferroelectric material layer of 2 layers in total formed by stacking layer B-layer C, or an antiferroelectric material layer of 3 layers in total formed by stacking layer A-layer B-layer C, or an antiferroelectric material layer of 5 layers in total formed by stacking layer A-layer A-layer B-layer C-layer C, or an antiferroelectric material layer of 7 layers in total formed by stacking layer A-layer A-layer A-layer B-layer C-layer C-layer; Alternatively, the multilayer antiferroelectric material layer is formed by periodically stacking layer A-layer B, or by periodically stacking layer B-layer C, or by periodically stacking layer A-layer B-layer C, or by periodically stacking layer A-layer A-layer B-layer C-layer C, or by periodically stacking layer A-layer A-layer A-layer B-layer C-layer C.

3. The antiferroelectric multilayer capacitor having a heterostructure as claimed in claim 1, characterized in that: The thickness of each antiferroelectric material layer itself does not exceed 50 μm.

4. The antiferroelectric multilayer capacitor having a heterostructure as claimed in claim 1, characterized in that: For the electrodes inside the multilayer antiferroelectric material layer, two adjacent electrodes are staggered in the left and right directions, so that an interdigitated electrode structure is formed as a whole; Antiferroelectric material sacrificial layers are stacked above and below the multi-layer antiferroelectric material layers.

5. The method for preparing an antiferroelectric multilayer capacitor having a heterostructure according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Preparing antiferroelectric material powder with large electro-strain and antiferroelectric material powder with small electro-strain, respectively, and subjecting them to tape casting to obtain antiferroelectric material monolayer film with large electro-strain and antiferroelectric material monolayer film with small electro-strain; then, slicing and cutting these monolayer films, and printing metal as an electrode on the upper surface of the cut monolayer film by screen printing; Among them, the antiferroelectric material with large electro-induced strain is (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 )O3 antiferroelectric ceramic material, the antiferroelectric material with small electro-induced strain is selected from (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 )O3 antiferroelectric ceramic materials, (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O3 antiferroelectric ceramic material; the value ranges of x, y, z, m, n, and p are all 0.02 to 0.06; S2. stacking the single-layer films with electrodes from bottom to top, so that except for the upper end face and the lower end face, the upper layer and the lower layer adjacent to each antiferroelectric material single-layer film with large electro-strain are both antiferroelectric material single-layer films with small electro-strain, and then hot pressing to obtain a capacitor green body with a multi-layer heterostructure, and performing cold isostatic pressing treatment; S3. The green body after cold isostatic pressing is subjected to binder removal treatment to remove organic matter introduced during the casting process, and then sintering treatment is performed. After cooling, silver electrode slurry is coated on the left and right end surfaces, and the end electrodes are prepared by sintering to obtain an antiferroelectric multilayer capacitor with a heterogeneous structure.

6. The preparation method according to claim 5, characterized in that: In step S2, before the hot pressing, it also includes making antiferroelectric material sacrificial layers above and below the stacked structure; In step S3, the burning end is specifically heated to 600°C at 5°C / min, kept at that temperature for 10-30min, and cooled along with the furnace.

7. The preparation method according to claim 5, characterized in that: In step S1, (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 )O3 antiferroelectric ceramic materials are based on (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 )O3 is prepared by mixing raw materials of PbO, BaCO3, La2O3, ZrO2 and SnO2 in the nominal chemical dosage ratio of the metal elements in the raw materials, followed by a first ball milling treatment and a first drying; then pre-calcining, and a second ball milling treatment and a second drying are performed to obtain (Pb 1-m-1.5y Ba m La y )(Zr 0.6 Sn 0.4 )O3 antiferroelectric ceramic materials; (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 )O3 antiferroelectric ceramic materials are based on (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 )O3 is prepared by mixing raw materials of PbO, BaCO3, La2O3, ZrO2, SnO2 and TiO2 in the nominal chemical dosage ratio of the metal elements in the raw materials, and then performing the first ball milling treatment and the first drying; then pre-calcining, and performing the second ball milling treatment and the second drying, so as to obtain (Pb 1-n-1.5x Ba n La x )(Zr 0.65 Sn 0.3 Ti 0.05 )O3 antiferroelectric ceramic materials; (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O3 antiferroelectric ceramic material is based on (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 The raw materials of PbO, CaCO3, La2O3, ZrO2 and SnO2 are mixed in the nominal chemical dosage ratio of the metal elements in O3, and then subjected to the first ball milling treatment and the first drying; then pre-calcined, and subjected to the second ball milling treatment and the second drying, to obtain (Pb 1.01-p-1.5z Ca p La z )(Zr 0.6 Sn 0.4 ) 0.995 O3 antiferroelectric ceramic material.

8. The preparation method according to claim 7, characterized in that: For each antiferroelectric ceramic material: The ball milling speed of the first ball milling treatment is 200-500 r / min, and the ball milling time is 3-48 h; The drying temperature of the first drying is 50-110°C and the drying time is 3-12h; The pre-burning temperature is 800-950°C and the pre-burning time is 2-5h; The ball milling speed of the second ball milling treatment is 200-500 r / min, and the ball milling time is 3-48 h; the drying temperature of the second drying is 50-110° C., and the drying time is 3-12 h.

9. The preparation method according to claim 5, characterized in that: In step S1, the casting process is to disperse the corresponding antiferroelectric ceramic material powder together with a dispersant, a defoamer, a binder and a plasticizer in a solvent, and mix them by ball milling at a speed of 200 to 500 r / min for 3 to 48 hours to obtain a casting slurry, and vacuum degassing for 10 to 60 minutes. At a speed of 0.5 to 5 m / min, the casting slurry is cast on a casting machine and dried to obtain a single-layer film; Preferably, the thickness of the single-layer film obtained by casting is 5 to 50 μm.

10. The preparation method according to claim 5, characterized in that: In step S2, the metal is silver, palladium, copper, nickel, platinum or an alloy of two or more thereof; the thickness of the screen-printed electrode is 0.5 to 3 μm; The hot pressing treatment temperature of the hot pressing is 60-80°C, the pressure value is 2-20Mpa, and the holding time is 1-30min; The pressure value of cold isostatic pressing treatment is 50-200Mpa, and the holding time is 10-30min; In step S3, the debinding treatment is carried out at a temperature of 500 to 600° C. for 30 to 300 minutes; The sintering process is carried out at a temperature of 1100-1200° C. for 2-6 hours.

Citation Information

Patent Citations

  • Lead-free epitaxial multi-layer thin film having high energy storage density and favorable thermal stability and preparation method of lead-free epitaxial multi-layer thin film

    CN109082642A

  • Preparation method of heterogeneous stacked multilayer ceramic capacitor with antiferroelectric material system

    CN110803928A

  • MLCC pulse power capacitor of anti-ferroelectric material system and preparation method

    CN113077985A

  • Multilayer capacitor

    CN114375481A

  • Antiferroelectric capacitor

    US20220301785A1